Anesthetic Management of Critical COVID-19 Infection: A Narrative Review of Concepts and Evidence-Based Clinical Practices - Jameel Kassam; Eapen Mathew (Global Journal of Anesthesiology - Peertechz Publications, 2022)
Anesthesiologists are on the frontline in the war against the global COVID-19 pandemic, providing airway, ventilatory, and hemodynamic support to acute patients suffering from severe and critical COVID-19 infection.